Acute Pancreatitis in Children : A Review Article - Musabbir, Nadira; Karim, ASM Bazlul; Sultana, Kaniz; Anwar, Syeda Afria (Northern International Medical College Journal, 2017)
The incidence of acute pancreatitis (AP) in children has significantly increased in the past two decades. However, it can be associated with severe morbidity and mortality. Therefore it should be considered in every child presented with unexplained severe abdominal pain. The etiology, clinical manifestation, and course of acute pancreatitis in children are often different than in adults. Therefore the early and effective diagnosis of acute pancreatitis in children is challenging. In this review, we will discuss the etiology, clinical features and laboratory testing for the disease and also the management outlines of acute pancreatitis in children. Northern International Medical College Journal Vol.8(2) January 2017: 235-238